KUALITAS PERAIRAN ANAK SUNGAI NGASO DI KABUPATEN ROKAN HULU BERDASARKAN BIOINDIKATOR ALGA - -, Afridayanti; Purnama, Arief Anthonius; Mubarrak, Jismi (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study about Ngaso River qater quality in Rokan Hulu based on algae as bioindicator has been conducted in July to November 2014 with purposive sampling method. Samples were collected using a plankton net no. 25 and brush muller. Result, 6 species were found. The highest abundance value in station 1 with 1526.55 cells/liter, the lowest in stations 3 with 22.4 cells/liter. The highest diversity index in station 1 with 0.35, the lowest in station 3 with 0.04. The highest dominance in station 1 with 3.21, the lowest in station 3 with 0.0001. Conclution, this river was in heavily polluted category.